EVALUATION OF MODIFIED UNILATERAL NASOPLASTY IN PATIENT WITH POST OPERATION OF UNILATERAL LABIOPLASTY AT MALAHAYATI HOSPITAL BANDA ACEH: COHORT STUDY FROM 2017-2019 - Taslima, Devyana Enggar; Taufik, Muhammad; Jailani, Muhammad; Rizal, Syamsul; Amirsyaha, Mirnasari (Jurnal Rekonstruksi dan Estetik, 2020)
Highlights: The study's outcomes reveal favorable results regarding nasal enhancement following rhinoplasty, disparities in surgical choices, and variations in patient gender distribution. It is essential to recognize that these preliminary findings, while encouraging, underscore the necessity for additional documentation and research. Abstract: Introduction: Nasal deformity associated with cleft lip has been viewed as one of the most challenging reconstructive problems in rhinoplasty. The common clinical features associated with cleft lip nasal deformity are its lack of symmetry, alar collapse on the affected side, short nasal length, loss of tip definition, obtuse nasal labial angle, and altered columella show among others. The complexity of cleft lip rhinoplasty is demonstrated by the an abundance of technique that is available for its correction. In this case weused the technique modified by Dr. Muhammad Jailani, SpBP-RE in Aceh. Methods: We conducted a retrospective study involving 139 patients who is done the rhinoplasty unilateral operation at Malahayati Hospital from January 2017 to November 2019. Demographic information was recorded such as a ratio between pre–operation and post–operation, gender, and age. Results: Our results has shown the result of comparison between cleft nose before rhinoplasty and cleft nose after rhinoplasty is ±0.26 : ±0.58, and the patients who came to the hospital for rhinoplasty unilateral surgery are 81% of 139 patients. Women (61.2%) experience rhinoplastymore dominant compared to man (38.8%), and the highest age average is between 1 year until 7 years old (71%) Conclusions: Improvement in procedure's duration and better positioning of both nasal tip and nostril. Expected improvements in terms of aesthetic and functions were observed but further documentations still needed.